The level of professionalism and the use of PMS among managers in Malaysia manufacturing firms / Nurul Ashikin Said, Amizawati Mohd Amir and Ruhanita Maelah. - Said, Nurul Ashikin; Mohd Amir, Amizawati; Maelah, Ruhanita (Accounting Research Institute and UiTM Press, 2017)
Nowadays, stringent competition has forced the manufacturing sector to focus on performance measurement systems (PMS) to ensure individual employee’s actions are in line with organizational objectives. Accordingly,the individual level of professionalism is seen as one of the elements to be considered to enhance the use of PMS. Looking from the individuallevel perspective, this study aims to examine the relationship betweenprofessionalism with the use of PMSand their impact on managerial performance. Upper Echelon Theory (UET) is used as the underlying principle in developing the model of the study. UET suggests personalcharacteristics such as expertise and specialization are crucial in dealing with complex and complicated decision making processes and consequently affect performance. Data were collected through a mail questionnairefrom 100 operation managers of manufacturing firms. Path models were analyzed using structural equation model (SEM). Findings indicate the level of managers’ professionalism positively affects the use of PMS for attention focus and strategic decision making. The result also suggests that the use of PMS for strategic decision making positively affects managerial performance. In addition, results indicate that PMS used for strategic decision making has a mediating effect on the relationship between professionalism and managerial performance. This study provides new insights into the improvement of PMS by considering individual elements such as level of professionalism of managers and contributes to the body of knowledge.